Design and Implementation of a Database and RBAC for Scientific and Competency Mapping Web-based Information System for Lecturers at UPN “Veteran” Jawa Timur - Tresna Maulana Fahrudin; Achmad Yusuf Al Makruf (Future Science, 2023)
Scientific and competency mapping web-based information system aims to address several relevant issues within the context of the Tri Dharma framework in higher education, specifically at UPN